Modification of treaties by subsequent practice - Buga, Irina, 1988- (Oxford, United Kingdom : Oxford University Press, 2018)
This book explores the process of treaty modification by subsequent practice, explaining how such practice can significantly revise treaty obligations or even create new ones, allowing evolution of the law.
Introduction -- Subsequent practice as a means of treaty interpretation -- Subsequent practice as a means of treaty modification -- Subsequent customary law as a means of treaty modification -- A systematic analysis of examples of modification by subsequent practice -- Conclusion.
Includes bibliographical references (pages 375-407) and index.
Keywords: Vienna Convention on the Law of Treaties; Treaties -- Interpretation and construction; Treaties -- Revision; Sources of international law; Treaties -- Interpretation and construction; Treaties -- Revision